PENGARUH BERBAGAI PARAMETER PADA PROSES PEMINTALAN TERHADAP KARAKTERISTIK MEMBRAN SERAT BERONGGA DARI POLISULFON - RATNAYANI, OKA
Hollow fiber membranes were prepared by dry-wet spinning using phase inversion technique by immersionprecipitation. The casting solution consists of polysulfone ( PSf), N.N-dimethylacetamide (DMAc), and polyethylene glycol (PEG) as the additive. Water was used as internal and external coagulation agent as well. The effect of various spinning parameters on membrane performance, morphology, and mechanical strength have been studied in this research to obtain the optimum characteristics of the membranes. These parameters were as follows: air gap varied from 2 cm to 25 cm, internal coagulant flow rate increased from 40 mL/minute to 100 mL/minute, applied pressure to casting solution varied from 0.2 to 1 atm, composition of solvent (DMAc) in the internal coagulant varied from 10% to 50%, temperature of casting solution increased from 29Â°C to 55Â°C, and composition of PSf and PEG varied from 17% to 19% w/w. This work showed that longer air gap result in higher permselectivity but lower permeability due to the thicker skin layer of the membranes. The increase of internal coagulant flow rate tends to produce thinner membranes with larger pores, and hence, increase the permeability. The increase of applied prossure to casting solution tends to produce thicker membranes that leads to a decrease of permeability but an increase of permselectivity. The existence of solvent in the internal coagulant results in a sponge like sublayer and dense skin layer which causes a lower permability and a higher permselectivity of the membranes. However, using a composition of 50% DMAc in the internal coagulant dissolves the polymer on the membrane surface and produces higher permeability and lower permselectivity. Increasing the temperature of the casting solution increases the solvent evaporation rate from dope solution. PSf concentration in the casting solution tends to increase the viscosity of the solution leads to produce higher permselectivity but lower permeability. On the other hand, higher concentration of additives increases the number of pores but the permselectivity remains constant.